STRATEGY TO BUILD WELFARE OF THE INDONESIAN-TIMOR LESTE POPULATION BORDER IN NUSA TENGGARA TIMUR AS A FORM OF STATE DEFENSE - Gita Sari Dewi; Zainal Abidin Sahabuddin; Susilo Adi Purwanto (JISOS: JURNAL ILMU SOSIAL, 2023)
Indonesia has land and sea borders with ten countries, one of which is the country of Timor Leste which borders on land with the Province of East Nusa Tenggara (NTT)-Indonesia. Initially, Timor Leste was the eastern part of the Unitary State of the Republic of Indonesia, but was separated and officially became its own country under the name of the Democratic Republic of Timor Leste (RDTL) in 2002. One of the reasons for the loss of Indonesia's territorial territory was the weak defense of the Indonesian state. The high and low level of welfare of the population of the border area is one indicator of assessing how strong a country's defense is, where if the welfare level of the population is high then the national defense will be strong and vice versa if the welfare level of the population is low then the national defense will be threatened. Based on the Human Development Index (HDI) issued by BPS in 2020, the border population of NTT HDI is still low at 65.19 when compared to the National HDI of 71.94. In this study, the authors use the SWOT and AHP methods to determine the strengths, weaknesses, opportunities and threats of residents of the border areas of NTT. The results of the study found that the NTT border area has a lot of potential to be developed and weaknesses in the form of the quality of human resources and capital are still lacking and from the analysis of these factors a strategy is produced as an effort to improve the welfare of border communities, namely (1) facilitating education to prepare competent border residents, ( 2) facilitating health to reduce maternal & infant mortality and the number of sick people, (3) reviving cooperatives as a forum for community capital, (4) developing the agricultural, plantation and livestock sectors which are the main livelihoods of border residents, (5) making a good market mechanism, (6) advancing the marine and tourism sector which previously had not been managed optimally